Strategies and challenges of adolescent twins in defining oneself as distinct from the other - Sale, Eilleen Keith Alfaro; Domingo, Trisha Celine P.; Roldan Aurorita Tan. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT The present study aimed to identify the strategies and challenges of adolescent twins in defining self as distinct from the other in the context of the family and peer groups. Non-probability purposive sampling was employed to gather identical and same-sex fraternal twin participants, who are 16-22 years old, presently or permanently residing Metro Manila. Face-to-face interviews with eight pairs of identical twins and eight pairs of fraternal twins (32 respondents) were conducted. The adolescent twins were interviewed individually to gain an account of the strategies and challenges they face along the course of building a sense of self apart from their twin. The study revealed that more identity-related challenges are experienced by adolescent twins in the context of the family and less in peer groups. Identical twins also reported more challenges and develop more strategies than fraternal twins. Lastly, it may be argued that having a twin predisposes an individual to take conscious efforts and actions to assert oneself. The findings of the present study provide insights and support existing literature about the significant role of the family as a socializing agent in the lives of adolescents as they go along the process of identity development. Given this, it is important that the family serve as a support group of adolescent twins as they go about the course of asserting their identity distinct from the other.
Thesis (B.S. Familky Life and Child Development)--University of the Philippines Diliman.
Keywords: Twins -- Psychology